Effect of antihistaminics on amplitude of rabbit gut - Prakash, Rashmi; Singh, Vinay; Kumar, Devesh; Haider, Jamal; Asthana, A. B.; Pandey, Pooja Tripathi (International Journal of Research in Medical Sciences, 2017)
Background: The small intestine, like the rest of the gastrointestinal tract, is an intelligent organ. It generates a wide variety of motor patterns to meet motility requirements in different situations. Its basic motor function after a meal is to mix the chyme with exocrine and intestinal secretions, agitate its contents too. Methods: In vitro study is done to explore the effect of 1st generation antihistaminic (chlorpheniramine maleate) and second generation antihistaminic (Fexofenadine) on amplitude of gut motility by isolated rabbit gut preparation on Dale’s Organ bath, part of terminal ileum is used for study. Eight rabbits weighing 2 to 4.5 kg were used for study. The effect of antihistaminic observed that both drugs reduce amplitude. Results: The effect of Chlorpheniramine malete and Fexofenadine on amplitude observed and it found that both decrease the amplitude significantly. Conclusions: This study establishes a correlation between amplitude of gut and effect of antihistaminic suggests that antihistaminic drug both first generation and second generation decreases the amplitude of gut motility with a significant response.